ANALISIS BENTUK DAN MAKNA TAṢGHĪR NON-NISBAH DALAM ILMU SHARAF - Adisti Putri Aryani (Jurnal Sathar, 2025)
This study aims to analyze the form and meaning of non-nisbah taṣghīr from the perspective of Sharaf science, and to see how this form is used in the Qur'an and Arabic literature. Taṣghīr is a form of word derivation in Arabic that functions to convey various meanings such as belittling, affection, insults, and admiration. The focus of the study is directed at non-nisbah forms, namely taṣghīr forms that do not refer to affiliation or nisbah, but rather emphasize changes in morphological structure and semantic and pragmatic meaning. The main data comes from the Qur'an version of the Indonesian Ministry of Religious Affairs, accompanied by references from classical Sharaf books and modern Arabic linguistic literature. The results of the analysis show that non-nisbah taṣghīr has a very complex linguistic and social function and remains relevant in contemporary Arabic language studies. This form is not only a morphological transformation, but also a communication strategy that reflects emotional and cultural relationships in Arab society.